Race, ethnicity, and place in a changing America - Frazier, John W.; Tettey-Fio, Eugene; Henry, Norah F. (Norah Fox) (State University of New York Press : Global Academic Publishing, 2016)
This book examines major Hispanic, African, and Asian diasporas in the continental United States and Puerto Rico from the nineteenth century to the present, with particular attention on the diverse ways in which these immigrant groups have shaped and reshaped American places and landscapes. Through both historical and contemporary case studies, the contributors examine how race and ethnicity affect the places we live, work, and visit, illustrating along the way the behaviors and concepts that comprise the modern ethnic and racial geography of immigrant and minority groups. While primarily addressed to students and scholars in the fields of racial and ethnic geography, these case studies will be accessible to anyone interested in race-place connections, race-ethnicity boundaries, the development of racialization, and the complexity of human settlement patterns and landscapes that make up the United States and Puerto Rico. Taken together, they show how individuals and culture groups, through their ideologies, social organization, and social institutions, reflect both local and regional processes of place-making and place-remaking that occur within and beyond the continental United States.
Keywords: Population geography -- United States -- History.; Cultural pluralism -- United States -- History.; Landscapes -- Social aspects -- United States.; Minorities -- United States.; United States -- Race relations -- History -- 20th century.; United States -- Ethnic relations -- History -- 20th century.; United States -- Race relations -- History -- 21st century.; United States -- Ethnic relations -- History -- 21st century.; United States -- Social policy.; Population geography.; Géographie de la population.; Géographie de la population -- États-Unis -- Histoire.; Diversité culturelle -- États-Unis -- Histoire.; Paysages -- Aspect social -- États-Unis.; États-Unis -- Relations raciales -- Histoire -- 20e siècle.; États-Unis -- Relations interethniques -- Histoire -- 20e siècle.; États-Unis -- Relations raciales -- Histoire -- 21e siècle.; États-Unis -- Relations interethniques -- Histoire -- 21e siècle.; États-Unis -- Politique sociale.; population geography.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Cultural pluralism; Ethnic relations; Landscapes -- Social aspects; Minorities; Population geography; Race relations; Social policy; United States; Einwanderer; Landschaft; USA; Puerto Rico; 1900-2099; History